Observations of radiation-enhanced ductility in irradiated Inconel 718: Tensile properties, deformation behavior, and microstructure. (1st June 2022) - McClintock, David A.; Gussev, Maxim N.; Campbell, Cody; Mao, Keyou; Lach, Timothy G.; Lu, Wei; Hachtel, Jordan A.; Unocic, Kinga A.
Abstract: An increase in ductility with radiation dose was observed and investigated during postirradiation evaluation of tensile properties, microstructure, deformation behavior, and fracture behavior of specimens from a solution-annealed Inconel 718 proton beam window operated at the Spallation Neutron Source. While in service, the window was irradiated with 940 MeV protons to a maximum dose of approximately 9.7 displacements per atom (dpa) at a calculated irradiation temperature of approximately 110 °C. The double-walled window was sampled after removal from service, and specimens from the samples were characterized using transmission electron microscopy and tensile testing accompanied by digital image correlation. The results showed that the window material had very high tensile strength and retained an appreciable amount of ductility after irradiation. Specimens irradiated to approximately 9 dpa had yield strengths of around 1 GPa while concurrently straining to approximately 19% total elongation before fracture. A steady increase in ductility was observed with increasing dose for the material tested; both uniform and total elongation values increased as the radiation dose increased from 2.5 to 9.7 dpa. High-resolution scanning transmission electron microscopy and electron energy-loss spectroscopy, performed at atomic resolution, showed the existence of nanometer scale stacking faults and nanometer size vacancy clusters associated with H and possibly He. These radiation-induced defect structures may have increased the ability of the material to strain-harden during deformation and increased the ductility with increasing dose. The results were encouraging and suggest that the mechanical performance of Inconel 718 after irradiation to 9.7 dpa is favorable and provided support to increase the proton beam window service lifetime to higher displacement dose levels. Graphical abstract: Image, graphical abstract